THE EFFORTS TO PREVENT CHILD KHALWAT VIOLATION BY WILAYATUL HISBAH IN LANGSA CITY - Marlina Marlina (Jurnal Pembaharuan Hukum, 2024)
The hildren are the nation's next generation who must be protected by the state and society so that children grow and develop. Normative juridical and empirical juridical research methods using in-depth interviews with WH, Islamic Sharia services, Sharia courts, the community and children. Research shows that Qanuns regarding the role of WH in preventing khalwat violations by children in Langsa include Qanun No. 6 of 2014 concerning Jinayat Law, Qanun No. 7 of 2013 concerning Jinayat Procedural Law, Qanun No. 11 of 2002 concerning Implementation of Islamic Sharia in the Sector of Aqidah, Worship and Sharia of Islam, Qanun 14 of 2003 concerning Khalwat, Law No. 11 of 2006 concerning Aceh Government Law, Law No. 5 of 2007 concerning Organizational Structure and Work Procedures of Services, Technical Institutions. Aceh Governor's Decree No. 1 of 2004 concerning the Organization and Work Procedures of Wilayatul Hisbah. The role of Wilayatul Hisbah in preventing khalwat violations is by providing guidance, supervision, implementation of Islamic law as well as raids and arrests through collaboration with the police, which are then submitted to the customary law. Obstacles faced by Wilayatul Hisbah in implementing the prevention of khalwat violations against children in Langsa include limited time to carry out supervision, lack of professionalism in carrying out tasks, limited budget, lack of public understanding about khalwat and lack of public legal awareness about the importance of Wilayatul Hisbah.